Measurement of the muon lifetime and the Michel spectrum in the LAGO water Cherenkov detectors as a tool to enhance the signal-to-noise ratio - Otiniano, L.; Taboada Nuñez, Alvaro; Asorey, Hernán Gonzalo; Sidelnik, Iván Pedro; Castromonte, C.; Fauth, A. (Elsevier Science, 2023)
Fil: Otiniano, L.. Universidad Nacional de Ingenieria; Perú